Identification and antibiotic susceptibility of enterococcus spp. from raw cow milk and raw goat milk / Siti Nor Zaleha Manaf - Manaf, Siti Nor Zaleha (Faculty of Applied Sciences, 2014)
Concerning to biohazard level caused by enterococcal infections, a study has been done to detect the prevalence of the Enterococcus spp. in raw milk from cow and goat since this species was known to be as a food-borne pathogen that primarily predominant in dairy products. Prior to detection of Enterococcus spp. the assumption on viable population count for presumptive Enterococcus spp. have been tabulated by which the raw cow milk isolates showing a high number compared to isolates from raw goat milk due to slightly different temperature storage. The identification to genera level has been carried out through 10 biochemical tests. For carbohydrate test, comprises of lactose, sucrose, glucose and maltose have shown positive result by which all the 25 isolates from both raw cow and goat milk were fermented. Further tests are also showing a comparable result to previous study, such as catalase test, potassium hydroxide test, Gram stain, growth at 10°C, 40°C and 6.5% NaCl. Enterococcus spp. is highly resistant, resulted in 100% resistant to 11 antimicrobial agents. This is due to consequence from the dissemination of multiple antibiotic-resistant enterococci or may be caused by their transferable genes. Besides, the extensive and provident use of antibiotics in animal husbandry and veterinary medicine could also affect the antibiotic resistant among the Enterococcus spp.